FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS BITUNG BARAT TAHUN 2023 - Tombokan, Vera Diane; Thalib, Hajira (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Hypertension is a common condition in primary health care with an increased risk of morbidity and mortality as blood pressure rises, which can lead to heart failure, stroke, and kidney failure. This condition is often referred to as the “silent killer” because it often shows no symptoms. In Indonesia, it is estimated that half of the people with hypertension are unaware of their condition. This study was conducted to determine the risk factors for hypertension at the West Bitung Health Center in 2023, using a quantitative method with a cross-sectional design. The study involved 97 respondents and analyzed the relationship between alcohol consumption, smoking habits, physical activity, and obesity with hypertension. The results showed that there was no relationship between alcohol consumption and smoking with hypertension, but there was a relationship between physical activity and obesity with hypertension. These findings can serve as a basis for further research on public perceptions of obesity and motivation to achieve an ideal body weight to reduce the incidence of hypertension.